(untitled) (Annals of Medical Research, 2021)
Aim: Thyroidal incidentalomas (Tis) detected by F-18 fluorodeoxyglucose positron emission tomography/computed tomography (F-18FDG PET/CT) may be associated with three different causes that include metastasis of another malignancy, primary thyroid gland malignancies and lastly benign thyroidal nodules, all require different clinical approaches. For appropriate treatment, quick characterization of the Ti is important, preferably with a lesser invasive method. Our aim was to determine whether the characterization of TIs can be performed with FDG-PET/CT, due to contribute faster diagnosis, and initiation of the therapy.Material and Methods: Forty-four patients with detected TIs in FDG-PET/CT were included in the study. The relationship between metabolically/morphological parameters and pathology results were evaluated statistically. If two subsequent cytology were negative, nodule accepted as benign. If cytology result was suspected or malignant, histopathological confirmation was made. For these patients, histopathological results were accepted as definite diagnosis. Results: Malignant thyroidal pathologies were detected in 29.5% of patients. We could not find any significant relationship between age, nodule size and SUVmax value and pathology results. According to ROC analysis, there were not any cut-off value for nodule size and SUVmax. Similar results were also obtained for papillary carcinoma as a special subgroup.Conclusion: Characterisation of TIs could not be performed by using age, nodule size and SUVmax. Therefore, TIs which detected by FDG-PET/CT should be examined pathologically due to high risk of malignancy.Keywords: Thyroidal incidentalomas; FDG-PET/CT; malignant; characterization.